A-type stars in the Canada–France Imaging Survey I. The stellar halo of the Milky Way traced to large radius by blue horizontal branch stars. Issue 4 (25th September 2018) - Thomas, Guillaume F; McConnachie, Alan W; Ibata, Rodrigo A; Côté, Patrick; Martin, Nicolas; Starkenburg, Else; Carlberg, Raymond; Chapman, Scott; Fabbro, Sébastien; Famaey, Benoit; Fantin, Nicholas; Gwyn, Stephen; et al.
ABSTRACT: We present the stellar density profile of the outer halo of the Galaxy traced over a range of Galactocentric radii in the range 15 < R GC < 220 kpc by blue horizontal branch (BHB) stars. These stars are identified photometrically using deep u -band imaging from the new Canada–France Imaging Survey (CFIS) that reaches 24.5 mag. This is combined with griz bands from Pan-STARRS 1 and covers a total of ∼4000 deg 2 of the northern sky. We present a new method to select BHB stars that has low contamination from blue stragglers and high completeness. We use this sample to measure and parametrize the three-dimensional density profile of the outer stellar halo. We fit the profile using (i) a simple power law with a constant flattening (ii) a flattening that varies as a function of Galactocentric radius (iii) a broken power-law profile. We find that outer stellar halo traced by the BHB is well modelled by a broken power law with a constant flattening of q = 0.86 ± 0.02, with an inner slope of γ = 4.24 ± 0.08. This is much steeper than the preferred outer profile that has a slope of β = 3.21 ± 0.07 after a break radius of $r_ b=41.4^{+2.5}_{-2.4}$ kpc. The outer profile of the stellar halo trace by BHB stars is shallower than that recently measured using RR Lyrae, a surprising result given the broad similarity of the ages of these stellar populations.